Multiscale, Multiphysics Modelling of Coastal Ocean Processes: Paradigms and Approaches - Tang, Hansong; Nichols, C. Reid; Resio, Donald T.; Wright, Don (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes papers on physical phenomena, such as wind-driven flows, coastal flooding, and turbidity currents, and modeling techniques, such as model comparison, model coupling, parallel computation, and domain decomposition. These papers illustrate the need for modeling coastal ocean flows with multiple physical processes at different scales. Additionally, these papers reflect the current status of such modeling of coastal ocean flows, and they present a roadmap with numerical methods, data collection, and artificial intelligence as future endeavors.